Sensory and nutritional quality of nonfat dry milk in long-term residential storage - Lloyd, M.A.; Zou, J.; Ogden, L.V.; Pike, O.A. (Journal of food science, 2004)
Twenty samples of regular and instant nonfat dry milk (NFDM) stored up to 29 y in residential locations at ambient conditions in Nr 10 cans were analyzed for sensory and nutritional quality. Overall acceptability hedonic scores varied widely (2.9 to 6.2), but all samples were considered acceptable for use in an emergency situation by most panelists. A 23-y-old sample with low oxygen was not significantly different from fresh samples in overall acceptability hedonic scores. There was no difference in overall acceptability between regular and instant NFDM. Amounts of available lysine (1.4 to 2.6 mg/100 g), thiamin (2.7 to 4.0 microgram/g), and riboflavin (12.7 to 20.2 microgram/g) were not significantly correlated with sample age.